Modelling the intention to use information and communication technologies among SMEs in Malaysia / Nik Ahmad Munaim Nik Kamaruzaman and Yang Hartini Jaapar - Nik Kamaruzaman, Nik Ahmad Munaim; Jaapar, Yang Hartini (Faculty of Business and Management, 2013)
In the recent era of economic globalization, acquiring information communication technology (ICT) to support business needs, regardless of business size, is a crucial need to exploiting the potential of technology. The aim of this research is to identify the factors that influence behavioural intention of Malaysian SMEs to use technology in their business. The independent variables consist in the conceptual research frameworks are perceived usefulness, effort expectancy, social influence, facilitating condition, attitude towards using technologies and security and privacy the dependent variable would be the SMEs behavioural intention towards using technologies. In collecting data, the researchers used the owner of SMEs in all different country in Malaysia. There are 100 samples selected using convenience method. The data collected was then tested on its reliability, and then further analyzed using descriptive analysis, Pearson’s correlation analysis, and coefficient regression analysis. Based from the results obtain in this research, some recommendations have been suggested by the researcher.